Analisis harga pokok produksi atas pembiayaan yang bersifat common cost dengan pendekatan variable costing di Kalakopi Manado - Bangun, Aron Karolina; Pusung, Rudy J.; Kalalo , Meily Y. B. (Yayasan Widyantara Nawasena Raharja, 2024)
Common costs are the costs obtained from the time the raw materials are processed to the product which can be separated according to the identity of each product. Variable Costing is a method used to calculate the cost of production which only involves variable costs. This research aims to analyze the cost of production for Common Cost financing using a Variable Costing approach in Kalakopi Manado. The type of research used is descriptive qualitative research and research data collection is carried out by means of interviews, observation and documentation. The results of the research show that calculating joint costs using a variable costing approach makes the cost of production of donuts smaller than the selling price set by the company.